2012
DOI: 10.1108/17439131211216620
|View full text |Cite
|
Sign up to set email alerts
|

Working capital management and firms’ performance in emerging markets: the case of Jordan

Abstract: PurposeThe purpose of this paper is to examine the effect of working capital management on firms’ performance for a sample of firms listed on a small emerging market, namely Amman Stock Exchange.Design/methodology/approachThe paper includes a conceptual as well as empirical analysis, in which data from a sample of listed firms for the period from 2000 to 2008 are analyzed to examine if more efficient working capital management improves firms’ accounting profitability and firms’ value. Cash conversion cycles as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
223
8
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(279 citation statements)
references
References 35 publications
37
223
8
11
Order By: Relevance
“…Varying explanation has been given by different researchers on the direction of the relationship between WCM and firm value. While some studies (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;De Almeida & Eid jr, 2014;Lifland, 2011;Wasiuzzaman, 2015) argue that the reduction in WCM increases firm value, other studies (e.g., Abuzayed, 2012;Ali & Ali, 2012;Lyroudi & Lazaridis, 2000;Rimo & Panbunyuen, 2010) also argue that higher working capital increases firm value.…”
Section: Working Capital Management and Firm Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Varying explanation has been given by different researchers on the direction of the relationship between WCM and firm value. While some studies (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;De Almeida & Eid jr, 2014;Lifland, 2011;Wasiuzzaman, 2015) argue that the reduction in WCM increases firm value, other studies (e.g., Abuzayed, 2012;Ali & Ali, 2012;Lyroudi & Lazaridis, 2000;Rimo & Panbunyuen, 2010) also argue that higher working capital increases firm value.…”
Section: Working Capital Management and Firm Valuementioning
confidence: 99%
“…While some studies found a negative relationship between WCM and firm value (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;De Almeida & Eid jr, 2014;Kieschnick et al, 2008;Kieschnick et al, 2013;Lifland, 2011;Mohamad & Saad, 2010;Wasiuzzaman, 2015), others found a positive relationship (e.g., Abuzayed, 2012;Ali & Ali, 2012;Lyroudi & Lazaridis, 2000;Rimo & Panbunyuen, 2010). Varying explanation has been given by different researchers on the direction of the relationship between WCM and firm value.…”
Section: Working Capital Management and Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In this connection OECD (2006) indicates that the corporations' working capital was affected by the inclusive financial crises meanwhile these companies confronted growing in their debtors collection period and inventories transformation period due to the falling in the demand for their products, which replicated negatively their working capital and hence their liquidity (Abuzayed, 2012). Particularly, Garcia-Teruel and Martinez-Solano (2007) identify that cash conversion cycle (hereafter CCC), which considered as a key factor in WCM, refers to -the average number of days between the date when the firm must start paying its suppliers and the date when it begins to collect payments from its customers‖.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…Sales growth is negatively related to working capital management before and after the crisis periods. (Abuzayed, 2012) The financial crises of 2008 and recession brought focus of industries towards the investments in short term assets and resources which have a maturity of less than one year. This flamed the importance of working capital management at companies all over the world.…”
Section: Importance Of Trade Credit For Sme'smentioning
confidence: 99%